2020
DOI: 10.15536/thema.v18.especial.2020.319-331.1798
|View full text |Cite
|
Sign up to set email alerts
|

Influência do acesso a saneamento básico na incidência e na mortalidade por COVID-19

Abstract: A falta ou a escassez de saneamento básico pode causar consequências negativas à saúde de uma população. Esta pesquisa objetivou analisar a influência do acesso a abastecimento de água e a esgotamento sanitário na incidência e na mortalidade por COVID-19, pelo uso de regressão linear múltipla. Utilizaram-se dados de população urbana e total relativas aos estados brasileiros e foram testados 4 cenários para se avaliar a influência desses dados nas taxas de incidência e de mortalidade por COVID-19 acumuladas 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
4
0
3
Order By: Relevance
“…It is noteworthy that in this study they considered the statistical significance to be 90%. In another study carried out for all Brazilian states, the results showed no statistical significance between the mortality rates of patients with COVID-19 and the indicators of water supply and sanitation ( Aquino, 2020 ). On the other hand, Silva et al.…”
Section: Resultsmentioning
confidence: 89%
“…It is noteworthy that in this study they considered the statistical significance to be 90%. In another study carried out for all Brazilian states, the results showed no statistical significance between the mortality rates of patients with COVID-19 and the indicators of water supply and sanitation ( Aquino, 2020 ). On the other hand, Silva et al.…”
Section: Resultsmentioning
confidence: 89%
“…The study area encompassed 626 municipalities in the São Paulo State (SP), Brazil. The municipal quantitative indicators for sanitation and COVID-19 were based on previous studies (AQUINO, 2020;SILVA et al, 2020). Seven sanitation indicators (Table 1) were retrieved from the National Sanitation Information System database (SNIS, 2021), considering the last available data update (i.e., in 2019).…”
Section: Study Area Data Source and Collectionmentioning
confidence: 99%
“…Recent studies have pointed out that the sanitation indicators may correlate with the Covid-19 cases (e.g., incidence and lethality) (AQUINO, 2020;SILVA et al, 2020). In such a pandemic scenario, managers and service providers can include indicators in strategic management and decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Diferentes trabalhos com manipulação de dados da COVID-19 e do saneamento foram realizados, concluindo que a presença dos sistemas gera redução na ocorrência de casos de COVID-19 (AQUINO, 2020;EKUMAH et al, 2020;SILVA et al, 2021;CARNIEL, 2022). Aquino (2020) e Silva et al (2021) alcançaram conclusão semelhante à do presente trabalho a respeito do impacto da cobertura de esgoto no Brasil com relação à proliferação do novo coronavírus, verificando que a presença de sistemas de saneamento tende a provocar redução na ocorrência de casos e O estudo conduzido por Cambaza (2021) com dados da COVID-19 e do saneamento em cidades de Moçambique apresenta resultados semelhantes aos alcançados no presente trabalho para o abastecimento de água. O autor verificou, pela aplicação de modelo estatístico, correlação positiva entre índices de saneamento, tanto de cobertura de esgotamento sanitário quanto de abastecimento de água para consumo humano, e de casos confirmados de COVID-19.…”
Section: Normalunclassified